Comparing Adolescent Bullying Behavior Across Parenting Styles and Residential Area - Tuğba YILMAZ; İrem Derya ÇAĞLAYAN (Nesne Psikoloji Dergisi, 2018)
Bullying constitutes major problems in the schools in Turkey as well it does all around the world. One of the complex reasons for bullying is considered to be living in rural or urban areas. For this study, data were collected from the Çankırı province as the rural area and the Ankara province as the urban area. The study was conducted with participants from regular high schools, between ages of 14 and 18. The study included 246 participants of which are 145 female and 101 male students. Participants were asked to complete the Demographic Information Form, The Bully/ Victim Questionnaire, The Self-esteem Scale, and The Parenting Style Inventory, in this order. The data obtained were then evaluated by comparative statistical analyses (t-test and ANOVA). The behavior of the bully or the victim did not significantly differ for rural and urban areas. However, four different parenting styles are demonstrated to have a significant effect on other variables. The limitations and implications of the study were discussed